(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
In this article, the system of kinship terms in English, Russian and Uzbek languages is studied from a comparative-typological point of view. The main goal of the research is to determine the lexical-semantic features of kinship relations in different languages and to reveal their connection with cultural codes. In the work, the issues of inter-linguistic lacunae and semantic differentiation are highlighted through a comparative analysis of the terms "amaki" and "tog’a" with the English "uncle" and the Russian "дядя". As a result, the fact that the kinship system in the Uzbek language has a hierarchical and paternalistic character, and the dominance of linear and functional models in the English and Russian languages has been scientifically substantiated.